Neural Functions of Hypothalamic Oxytocin and its Regulation. (May 2022) - Wang, Ping; Wang, Stephani C.; Liu, Xiaoyu; Jia, Shuwei; Wang, Xiaoran; Li, Tong; Yu, Jiawei; Parpura, Vladimir; Wang, Yu-Feng
Oxytocin (OT), a nonapeptide, has a variety of functions. Despite extensive studies on OT over past decades, our understanding of its neural functions and their regulation remains incomplete. OT is mainly produced in OT neurons in the supraoptic nucleus (SON), paraventricular nucleus (PVN) and accessory nuclei between the SON and PVN. OT exerts neuromodulatory effects in the brain and spinal cord. While magnocellular OT neurons in the SON and PVN mainly innervate the pituitary and forebrain regions, and parvocellular OT neurons in the PVN innervate brainstem and spinal cord, the two sets of OT neurons have close interactions histologically and functionally. OT expression occurs at early life to promote mental and physical development, while its subsequent decrease in expression in later life stage accompanies aging and diseases. Adaptive changes in this OT system, however, take place under different conditions and upon the maturation of OT release machinery. OT can modulate social recognition and behaviors, learning and memory, emotion, reward, and other higher brain functions. OT also regulates eating and drinking, sleep and wakefulness, nociception and analgesia, sexual behavior, parturition, lactation and other instinctive behaviors. OT regulates the autonomic nervous system, and somatic and specialized senses. Notably, OT can have different modulatory effects on the same function under different conditions. Such divergence may derive from different neural connections, OT receptor gene dimorphism and methylation, and complex interactions with other hormones. In this review, brain functions of OT and their underlying neural mechanisms as well as the perspectives of their clinical usage are presented.